Semantic memory and creative evaluation - Amit Skurnik; Rakefet Ackerman; Yoed N. Kenett (BMC Psychology)
Abstract Background Creativity is a fundamental cognitive skill enabling the generation of original and effective ideas. While research has focused on creative idea generation, relatively little is known about creative idea evaluation, particularly from a metacognitive perspective. Understanding how knowledge structures relate to metacognitive processes that accompany creative thinking can further elucidate its complexity. Methods Using the relatedness judgment task, we constructed participants’ (N = 106) semantic memory networks. These networks provide individual-level measures such as network integration (efficiency), local connectivity, and community structure. These metrics were related to participants’ performance in the alternative uses task (AUT), which was used to assess both creative performance and participants’ subjective judgments of the originality of their responses. Results Objective originality was predicted by semantic memory networks that were broadly connected and avoided tightly knit clusters. In contrast, originality judgments were predicted by semantic memory networks that were highly integrated and efficient. These findings suggest a dissociation between objective originality performance and individuals’ self-assessments of originality. Finally, the number of ideas generated in the AUT was a consistent and strong predictor of both creative performance and individuals’ self-assessments of originality. Conclusions Our findings reveal how different aspects of semantic memory structure contribute to creative thinking and metacognitive judgments.